How social context impacts on women's fears of childbirth: A Western Australian example - Fisher, C.; Hauck, Yvonne; Fenwick, Jennifer (ELSEVIER, 2006)
This paper addresses the limited sociological understanding of the phenomena of childbirth fear using data from a qualitative research project conducted in Western Australia. This qualitative study used an exploratory descriptive design, with 22 women identified as being fearful of birth participating in an in-depth interview. Data analysis using the method of constant comparison revealed that social context, explored within the framework of the medicalisation of childbirth, and the intervening circumstances in which the women gave birth, impacted on how and why they experienced fear. As such, this paper argues that fear of childbirth has social as well as personal dimensions and is both a prospective and retrospective phenomena.The analysis identified prospective fear as both social and personal. The social dimensions were labelled as 'fear of the unknown', 'horror stories' and 'general fear for the well-being of the baby'. Personal dimensions included the 'fear of pain', 'losing control and disempowerment' and 'uniqueness of each birth'. Retrospective fear was exclusively personal and was clustered around the themes of 'previous horror birth' and 'speed of birth'. The analysis also revealed two central factors that mediated against childbirth fear: positive relationships formed with midwives, and the support women received from their informal network. Understanding and unpacking the dimensions of women's childbirth fear, and understanding the nature of relationships that mediate women's fear, provides health care professionals with information on which to base potential intervention strategies and support women in ways that lessen rather than heighten their fear.